U UJI DISOLUSI TERBANDING ANTARA SEDIAAN TABLET RAMIPRIL GENERIK DAN BERMEREK - Noorjannah Noorjannah; Noval Noval (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
Introduction: Ramipril is a medicine that used as hypertension medication, kidney failure. Ramipril is one of the medicines that needs to be comparable dissolution tested which has been regulated in the Regulation of the Drug and Food Control Agency Head Number HK.03.1.23.12.11.12017 year 2011 regarding Obligatory Comparable Dissolution Test. The comparable dissolution test used to make sure the equivalence and characteristics of a medicinal product of 2 samples or more. Purpose: To find out the physique quality and the profile difference of comparable dissolution speed between generic and branded ramipril. Methods: This research was conducted using the Cross Sectional design with correlation learning between risk factor and effect with conducting an approach. The risk factor is the generic and branded ramipril. Meanwhile, the effect factor is the effect that caused by the result of the comparable dissolution test. The data were analyzed using One Way Anova test. Results: In the research, the result of the conducted physique quality test on four samples is already qualified. In the dissolution test, sample 1 (generic) compared with the branded samples which are sample 2, sample 3, and sample 4 that have different dissolution speed. The lowest dissolution speed is in the generic sample which is sample 1 and the highest dissolution speed is in the branded sample which is sample 4. Conclusion: The result of the physique quality test is already qualified, meanwhile the result of the dissolution test is that there is a profile difference of dissolution speed between generic and branded samples. Keyword: Generic and Branded Ramipril, Comparable Dissolution